PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Sholihah, Dzakiyyah; Kartono, Kartono; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research aims to investigate the influence of the Problem Based Learning Model on the critical thinking abilities of fifth-grade students at State Elementary School 11 Pontianak Kota in the object of Natural and Social Sciences. The research employed an Experimental Method, specifically a Quasi Experimental Design using Nonequivalent Control Group format. The population in this research consisted of all fifth-grade students. Sampling was carried out using a Probability Sampling Technique, specifically Saturated Sampling. Data were collected through measurement techniques using instruments in the form of written essay tests. Based on the results of hypothesis testing using the Paired Sample t-test formula, the tcount is 3.74 and the ttable (Î± = 5% and dk = n - 1 = 21) is 2.08, which means tcount > ttable, then ð» is rejected and is accepted. 0 ð»ð‘Ž The Effect Size calculation yielded a value of 0.58, which is categorized as moderate, therefore it can be concluded that the Problem Based Learning Model has a positive and significant impact on the critical thinking abilities of fifth-grade students at State Elementary School 11 Pontianak Kota in Natural and Social Sciences subjects.